The problem of evasion and failure of students in the regular degree course in Biological Sciences at Escola Normal Superior-UEA/ENS (Research, Society and Development, 2023)
In recent decades, graduation has become very accessible to the general population. During the process of intense demand for higher education courses, the number of students who dropped out, were in university retention and failed became alarming. Evasion, retention and failure can have several triggering causes, from financial problems, family problems, mental disorders, course curriculum, etc. There is an even more specific phenomenon to be discussed: evasion in undergraduate courses. The Pedagogical Project of the Degree in Biological Sciences states that since its implementation in 2006, it has trained 61 graduates in Biological Sciences out of a total of 227 who entered until 2009. Of this total, 65 are still active in the course completion phase , with pending issues in disciplines. Therefore, there is a significant dropout rate and university retention that is not problematized in the institution. Therefore, the following scientific problem to be investigated was launched: What factors lead students of the Licentiate Degree in Biological Sciences at Escola Normal Superior to drop out and fail? Therefore, a questionnaire was sent via e-mail to 200 students of the regular course of Licentiate in Biological Sciences at Escola Normal Superior (regulars and dropouts) in order to find out the reasons for dropping out of the course and failure. Of these, 112 responses were obtained. Data were processed within the parameters of qualitative research. As a result, there was a significant association between mental disorders and evasion/failure, as well as that there is an association between successive repetitions and evasion in the studied group.